2018
DOI: 10.1038/s41467-018-06866-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-limited association of disordered protein by non-native electrostatic interactions

Abstract: Intrinsically disordered proteins (IDPs) usually fold during binding to target proteins. In contrast to interactions between folded proteins, this additional folding step makes the binding process more complex. Understanding the mechanism of coupled binding and folding of IDPs requires analysis of binding pathways that involve formation of the transient complex (TC). However, experimental characterization of TC is challenging because it only appears for a very brief period during binding. Here, we use single-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 70 publications
(99 reference statements)
6
35
1
Order By: Relevance
“…Interestingly, the transition path times of ACTR/NCBD interaction is much longer than the transition path times of protein folding, indicating the presence of stable intermediate state along the binding process . Furthermore, the lifetime of transient complexes for ACTR/NCBD is also longer than that for barnase/barstar, consistent with previous simulation predictions …”
Section: Rate Constantssupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the transition path times of ACTR/NCBD interaction is much longer than the transition path times of protein folding, indicating the presence of stable intermediate state along the binding process . Furthermore, the lifetime of transient complexes for ACTR/NCBD is also longer than that for barnase/barstar, consistent with previous simulation predictions …”
Section: Rate Constantssupporting
confidence: 89%
“…Interestingly, the transition path times of ACTR/NCBD interaction is much longer than the transition path times of protein folding, indicating the presence of stable intermediate state along the binding process. 109 Furthermore, the lifetime of transient complexes for ACTR/NCBD is also longer than that for barnase/barstar, 110 consistent with previous simulation predictions. 85 It is noted that as the conformations of IDPs/IDRs are highly dynamic, electrostatic interactions between IDPs/IDRs and their targets during the encounter process may be different from those of the corresponding ordered proteins, which may be reflected from a recent study on the interactions between the colicin E3 rRNase domain (E3) and the immunity protein Im3 (Figure 2a).…”
Section: Molecular Recognition Featuressupporting
confidence: 87%
“…However, the contribution of net charge on a protein towards its ability to bring about ribosome aggregation needs further investigation. Recent studies have demonstrated that the disease associated intrinsically disordered proteins are highly charged and often rely on non-native electrostatic interactions for associating even with their appropriate cellular binding partners 35,36 . Such a tendency of engaging in promiscuous interactions might also lead to cytotoxicity.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Scattering experiments yield information on the overall sizes and extents of disorder (20,26). By site-specific labeling, fluorescence techniques report on the mean distances between different sites within a protein chain and the reconfiguration dynamics of the chain on the hundreds of ns timescale, as well as interactions between different protein chains (14,27,28). NMR spectroscopy, based on various types of experiments, remains the only biophysical technique for characterizing both conformations and dynamics of IDPs at a residue-level resolution across timescales from picosecond (ps) to second (24).…”
Section: Introductionmentioning
confidence: 99%